Penguatan Pemahaman Masyarakat terhadap Sejarah Cerita Panji sebagai Warisan Budaya Kediri melalui Seminar Nasional - Erna Fatmawati; Sheva Rahmadhani; Nara Setya Wiratama (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The Panji Story is one of the Intangible Cultural Heritage (ICH) that has historical, cultural, and local identity values, especially for the people of Kediri. However, currently, the community's understanding of the Panji Story tends to be limited and is often considered only as a romantic story, so that the historical and cultural values contained therein are not fully understood. This activity aims to strengthen the community's understanding of the Panji Story as a source of history and local cultural heritage through a national seminar. The activity was conducted in the form of a seminar involving presentations by expert speakers, interactive discussions, and question and answer sessions with participants from various backgrounds, such as students, the general public, and cultural activists. The results of the activity showed an increase in participants' understanding and awareness of the historical, cultural, and educational value of the Panji Story. Participants not only understood the diversity of versions of the Panji Story, but also began to view it as an important part of local cultural identity that needs to be preserved and sustained. This activity showed that national seminars can be an effective educational medium in building collective public awareness of the sustainable preservation of local history and culture.